ON SOME FEATURES OF ULTRASOUND REFLECTION WATER-SAMPLE IN AN INCLINED FALL (PHYSICAL MODELING) - Fedin Konstantin; Lukyanowa Alina; Kolesnikov Yuriy (Russian Journal of Earth Sciences)
In recent years, the analysis of the dependence of reflection coefficients on the magnitude of the angle of incidence of reflected waves has been successfully used in the practice of seismic research. AVO analysis is one of the methods of dynamic analysis that is used to estimate changes in the amplitude of reflected waves depending on the distance between the explosion points and the receivers. The AVO method is based on the analysis of the dependence of the reflection coefficients on the angle of incidence. In real conditions, this dependence can be determined, for example, by the roughness of the boundaries. This determines the relevance of studying the features of reflection coefficients on uneven boundaries on objects with well-controlled properties. The aim of the work is to determine the nature of the influence of different-scale roughness of seismic boundaries on the reflection coefficients of elastic waves. The work also used the technique of isolating standing waves to determine the wave velocity. As a result, graphs were obtained demonstrating the dependence of the reflection coefficients on the magnitude of the angle of incidence of reflected waves from a rough surface. Reflection coefficients were also obtained for the boundary of an isotropic medium in the direction of the isotropy plane and possible ways of applying the results were analyzed. Based on the data obtained, we can say that when the azimuth changes relative to the direction of the surface, the reflection coefficients change significantly only at the supercritical angles of incidence.